THE EFFECTS OF THE ETHANOL EXTRACT OF MAHONI SEEDS (Swietenia macrophylla King) ON THE DIABETIC RATS INDUCTED WITH STREPTOZOTOCIN - Sri Kadarsih, Lukman La Basy Sri Lestari S R (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
background: Hyperglycemia causes oxidative stress and lead to diabetes complications. MDA is the result of peroxyde lipids due to the increasing ROS and causes glomerular hypertrophy resulted in a decrease marked with the increasing filtrate rate with the increasing creatinine serum and the presence of protein in the urine. Swietenia macrophilla King has as antidiabetic activity of which its parts to be used are often seeds that contain saponins.Objective: The study was conducted to determine the effects on renal protection by observing the serum creatinine parameters, MDA, and urinary protein.Methods: The subjects were 30 Wistar strain white rats aged 6-8 weeks weighing 180-200 grams. The subjects were conditioned with 60 mg/kgBW streptozotocin induced diabetes. Subjects were grouped into the control group, the diabetes, the ethanol extract of mahogany seeds (S. macrophylla King) 50 mg/kgBW group, 100 mg/kgBW and 200mg/kgBW groups. The administering of ethanol extract of mahogany seeds (S. macrophylla King)  was conducted for ± 21 days and serum creatinine inspection parameters, MDA and urinary protein before and after the extract mahogany.Results: The study showed that within the group of ethanol extract of mahogany seeds (S. macrophylla King) 50 mg/kgBW, 100 mg/kgBW, 200 mg/kgBW there are decreasing levels of blood glucose, serum creatinine, urine protein MDA and significant with p <0.05 and ethanol extract of mahogany seeds (S. macrophylla King)  200mg/kgBW give effect best.Conclusion: Administering ethanol extract of mahogany seeds (S. macrophylla King) to Wistar strain rats can prevent complications towards impaired renal function by observing the decline of serum creatinine, MDA and urinary protein. Keywords : hyperglycemia, Swietenia macrophylla King, serum creatinine, MDA, urinary Protein.